Covid-19 Pandemic And Conventional Transbronchial Needle Aspiration In The Developing World (Indian Journal of Applied-Basic Medical Sciences, 2021)
Over the period of past 10 years endobronchial ultrasound guided transbronchial needle  aspiration (EBUS-TBNA) has gained much popularity among Indian Interventional  Pulmonologists. Unintentionally, the conventional TBNA is underutilized and the skill is fast  fading. (1, 2)  Incidentally, in the developing world the practice and upkeep of EBUS-TBNA is  extremely expensive. Besides, getting a prompt repair of a damaged EBUS scope is also  challenging. Needless to say, that this delay is further compounded by the COVID-19 pandemic and the lockdown of the country. It is also realized that the luxury of a spare or a loaner scope  is almost non-existent in India.
Keywords: (EBUS-TBNA); Unintentionally; COVID-19 pandemic